Emerging therapies targeting tumor vasculature in multiple myeloma and other hematologic and solid malignancies - Podar, Klaus; Anderson, Kenneth C. (Current cancer drug targets, 2011)
Research on the formation of new blood vessels (angiogenesis) in general and vascular endothelial growth factor (VEGF) in particular is a major focus in biomedicine and has led to the clinical approval of the monoclonal anti- VEGF antibody bevazicumab; and the second-generation multitargeted receptor kinase inhibitors (RTKIs) sorafenib, sunitinib, and pazopanib. Although these agents show significant preclinical and clinical anti-cancer activity, they prolong overall survival of cancer patients for only months, followed by a restoration of tumor growth and progression. Therefore, there is a clear need to increase our understanding of tumor angiogenesis and the development of resistance. In this review we discuss up-to-date knowledge on mechanisms of tumor angiogenesis, and summarize preclinical and clinical data on existing and potential future anti-angiogenic agents and treatment strategies for Multiple Myeloma (MM) and other hematologic and solid malignancies.
Gesehen am 23.12.2022